LEGAL STANDING SERIKAT PEKERJA DALAM MENGAJUKAN GUGATAN PADA PENGADILAN HUBUNGAN INDUSTRIAL (STUDI KASUS : PELANGGARAN HAK CIPTA ATAS NAMA DAN LOGO SERIKAT PEKERJA PADA PUTUSAN NOMOR 7/G/2017/PHI.JMB JUNCTO PUTUSAN MAHKAMAH AGUNG NOMOR 959 K/PDT.SUS-PHI/2017) - Andari Yurikosari; Karina Hosea (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Based on Article 87 of UU Number 2 of 2004 concerning Settlement of Industrial Relations Disputes and Article 25, 1 Letter b concerning Labor Unions, labor unions as legal counsel have the right to represent their members in the Industrial Relations Court. However, in practice, Industrial Court Judges and Supreme Court Judges (Decision Number 7/G/2017/PHI.Jmb and Decision of the Supreme Court Number 959 K/Pdt.Sus-PHI/2017) decide that the legal counsel of LBH KSBSI has no legal standing to represent workers at PT. Petaling Mandra Guna with the consideration that the legal counsel of LBH KSBSI has violated the copyright of name and logo (Decision Number 378-K/Pdt.Sus-PHI/2017). So that raises problems, how is the position of the union as a legal counsel related to the legal standing and  the legal efforts of the LBH KSBSI? From these problems, the authors examined the normative research method. The results of the study show that the Industrial Relations Court is not authorized to decide on cases of industrial disputes based on copyright infringement on the name and logo, because the problem is not its authority and competence. Regulations regarding restrictions on legal remedies are regulated in SEMA which do not include the type and hierarchy of legislation. It is better, LBH KSBSI immediately submit a legal action in the form of a new lawsuit, so as to obtain legal certainty and the legislature immediately includes provisions for limiting legal remedies at SEMA to UU  No. 2 of 2004 concerning Settlement of Industrial Relations Disputes.